Sustainability of Garlic Development in East Lombok Regency, West Nusa Tenggara - Anas Zaini; Anwar Anwar; Idiatul Fitri Danasari (Postgraduate, University of Mataram, 2024)
This research is intended to evaluate the degree of sustainability of garlic development in East Lombok Regency as well as finding levers for its sustainability. Data collection used interview methods and online questionnaires for 45 farmer respondents spread across Sembalun District as the main garlic producer in West Nusa Tenggara. Sustainability evaluation analysis was carried out using farmers' subjective approaches to four dimensions, namely ecology, economics, social, and policy. The research results concluded that the majority of garlic farmers (78%) stated that garlic development had a low level of sustainability and only 22 percent stated that it was moderately sustainable. The three dimensions with a low sustainability category were the economic dimension (0.40), ecology (0.29), and policy (0.27). Meanwhile, the social dimension was in the medium category with a sustainability index (SI) of 0.55. However, overall, the sustainability index was in the low category (SI= 0.37).